Comparative assessment of modified self-reported periodontal risk assessment model and periodontal risk assessment model among the adult population - Prashanth Vishwakarma; Prachi M Ray; Arun Dodamani; Asmita Hamand; Gaurav Mali; Vardhman Jain (Wolters Kluwer Medknow Publications, 2023)
Introduction: A high burden of periodontal diseases is seen in the adult population. Hence, it is important to monitor the risk and progression of periodontal diseases. Instead of using complex clinical periodontal risk assessment models, self-reported measures would be favorable for obtaining data in order to conduct research and surveillance of population over time on the progression of periodontitis. Our aim was to compare two tools for periodontal risk assessment, the originally described periodontal risk assessment (PRA) model given by Lang and Tonetti and the modified self-reported periodontal risk assessment model, in patients, depending upon can be changed to after. Materials and Methods: All the participants completed a questionnaire used for modified self-reported periodontal risk assessment model. Periodontal status of the participants was recorded using the periodontal risk assessment (PRA) model given by Lang and Tonetti. Results: Among 50 patients examined 28, 14, and eight were in low-, moderate-, high-risk groups, respectively, identified by self-reported periodontal risk assessment, whereas 34, 10, and six were in low-, moderate-, high-risk groups, respectively, when identified by the PRA model given by Lang and Tonetti. Receiver operating characteristic curve (ROC curve) showed an area under the curve (AUC) of 0.835, and it represents good predictability of self-reported periodontal risk assessment model. Conclusion: This is feasible method with self-reported measures; it is easier, of low cost, and requires less equipment for obtaining data for research and surveillance of the periodontal status of a population.